Novel green nanobio-based reagent for rapid visualisation of latent fingerprints on non-porous substrates immersed in a natural outdoor pond - Azman, Aida Rasyidah (2021)
Candida rugosa lipase (CRL) has been gaining attention in various bioindustries. Despite being commonly reported to have high affinity towards lipids, its potential utilisation for visualising latent fingerprints for forensic purposes remains in its nascent stage. Considering the evidential values of fingerprints during underwater criminal investigations and the need to visualise them using a user- and environmentally-friendly reagent, development of a novel, green, and rapid nanobiobased reagent (NBR) was deemed beneficial. Additional to the limited availability of fingerprint biotechnological reagents utilising CRL, they appeared lengthy with at least three different solutions, non-optimised and did not comply with the prevailing guidelines for fingerprint reagent development. Therefore, this research was aimed at developing a novel, green and optimised NBR for rapid visualisation of fingerprints on wet non-porous substrates, in compliance with the guidelines. This research involved characterisations of the NBR, Response Surface Methodology (RSM) optimisation, stability and sensitivity assays, as well as field assessment of the performance of NBR in a natural outdoor pond for up to four weeks of immersion. While characterisation of NBR using Attenuated Total Reflectance-Fourier Transform Infrared spectroscopy (ATR-FTIR) and Field Emission-Scanning Electron Microscope (FESEM) confirmed the successful attachment of CRL onto the nanosupports, Scanning Electron Microscope (SEM) analysis provided detailed representation of specific attachments of the NBR onto the lipid-lined fingerprint ridges. Semi-quantitative chromatographic analysis confirmed the presence of nhexadecanoic and octadecanoic acids in wet fingerprints immersed in stagnant tap water for 30 days under laboratory-controlled settings. Subsequently, bioinformatics studies supported the presence of hydrogen bonds between the residue of CRL and commonly reported lipids found in fingerprint constituents. It was found that the optimum conditions for preparing the NBR with University of Canberra (UC) comparative scale of 0 were; 100 mg of CRL, 75 mg of acid functionalised multiwalled carbon nanotubes and 5 h of immobilisation interval. Both stability and sensitivity assays revealed that the NBR was able to visualise wet fingerprints even after four weeks of storage as well as up to six-split depletion series with modified-Centre for Applied Science and Technology (m-CAST) absolute scale of 4 and UC comparative scale of 0 particularly on glass slides, respectively. Field assessment revealed better quality of NBR-visualised groomed split fingerprints, particularly on glass slides at four weeks of immersions with UC comparative and m-CAST absolute scales of +1 and 2, respectively when compared to that of Small Particle Reagent (SPR). Furthermore, greenness assessment of NBR revealed the Eco-Scale points of 76, indicating ‘excellent green analysis’. Hence, the potential of NBR as the future stateof- the-art green fingerprint visualisation technology is empirically supported.